UPAYA KELUARGA KARIR MEMBENTUK KELUARGA SAKINAH - Hamim, Mohamad (Program Studi Hukum Keluarga Islam, 2024)
A wife as a career woman has both positive and negative impacts on their home life. Therefore, forming a sakinah family for career women certainly has many challenges and obstacles. So far, the stigma that is often attached to society that women have to look beautiful, look beautiful, look gentle and be at home just by taking care of the household can be considered psychological violence. Thus, career women's efforts to build harmony. In order for the family to become a sakinah family, the strategy is to maintain the commitment obtained from the agreement between husband and wife and good communication between husband, wife and children. This commitment and communication are important for career women, because women who work in the domestic sector and in the public sector have limited time and energy to carry out both roles. Therefore, career women need support from the people closest to them so that life continues to run harmoniously